2020
DOI: 10.1007/s11356-020-10416-9
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to suboptimal ambient temperature during specific gestational periods and adverse outcomes in mice

Abstract: Exposure to suboptimal ambient temperature during pregnancy has been reported as a potential teratogen of fetal development. However, limited animal evidence is available regarding the impact of extreme temperatures on maternal pregnancy and the subsequent adverse pregnancy outcomes. Our objective in this study is to investigate the relationship between temperature and maternal stress during pregnancy in mice. This study used the Naval Medical Research Institute (NMRI) mice during the second and third pregnant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 59 publications
2
7
0
Order By: Relevance
“…This is similar to other studies which reported environmental factors such as air pollution exposure during the late pregnancy is more likely to cause LBW compared with other trimesters [55] . This may be due to fact that the last trimester is a period of accelerated fetal and placental growth [56,57] . Different from the increased risk of LBW, we found that the risk of SGA was not increased when exposed to extremely low ambient temperature.…”
Section: Discussionsupporting
confidence: 90%
“…This is similar to other studies which reported environmental factors such as air pollution exposure during the late pregnancy is more likely to cause LBW compared with other trimesters [55] . This may be due to fact that the last trimester is a period of accelerated fetal and placental growth [56,57] . Different from the increased risk of LBW, we found that the risk of SGA was not increased when exposed to extremely low ambient temperature.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, one study showed that prenatal exposure to 18°C in mice initiated fetal fat brown fat storage; whereby, cold temperatures experienced during the third trimester may initiate cold-stress-related changes in the placenta (50). Cold stress in mice during the prenatal period has also been associated with negative impacts on a number of neuroimmune pathways, particularly as it pertains to the maternal hippocampus (51) and placental changes following late in pregnancy exposure (52). Vasoconstriction in the winter months has been identified as one possible explanation (53), while others have proposed environmental exposures encountered in the month of conception as important determinants for eclampsia onset (54).…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have found that elevated maternal temperatures adversely affect vital developmental processes, such as cellular development and central nervous system development, and has been linked to spontaneous abortions (Edwards, 1986;Edwards et al, 2003). A study of pregnant mice showed that placental weight and diameter decreased at both higher and lower temperature exposures (Mayvaneh et al, 2020). Exposure to cold temperatures induces peripheral vasoconstriction, which has been hypothesised to alter blood flow to the placenta (Van Zutphen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%